2020
DOI: 10.3389/fimmu.2020.00120
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages/Microglia Represent the Major Source of Indolamine 2,3-Dioxygenase Expression in Melanoma Metastases of the Brain

Abstract: The remaining authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 76 publications
4
15
0
Order By: Relevance
“…We do not attribute the differences between the two cohorts to the higher number of melanoma-infiltrated lymph nodes included in EcM compared to other cohorts, because these distinct immune cell subsets were not significantly different between EcM in lymph nodes versus EcM in non-lymph nodes. Furthermore, craniotomy specimens from the UPMC cohort had not previously received radiation, much like in previous studies (31,37,38). We confirmed that gdT cells are variably present in MBM.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We do not attribute the differences between the two cohorts to the higher number of melanoma-infiltrated lymph nodes included in EcM compared to other cohorts, because these distinct immune cell subsets were not significantly different between EcM in lymph nodes versus EcM in non-lymph nodes. Furthermore, craniotomy specimens from the UPMC cohort had not previously received radiation, much like in previous studies (31,37,38). We confirmed that gdT cells are variably present in MBM.…”
Section: Discussionsupporting
confidence: 86%
“…The UNC-CH cohort is significantly smaller compared to the UPMC cohort, including the patient subset with high TILs and subsequent treatment with immune checkpoint inhibitors that trends to live the longest compared to all other groups. However, UNC-CH's sample size is comparable to other previously reported craniotomy datasets (31,37,38). Furthermore, OS was the only clinical endpoint that was used in this study.…”
Section: Discussionmentioning
confidence: 58%
“…In vitro stimulation of monocytes with IFNγ increased the M2/M1 ratio, while silencing of IDO in monocytes resulted in upregulation of pro-inflammatory M1-macrophages (74). In melanoma, macrophages constituted the predominant source of IDO expression in brain metastases (145). In agreement with these observations, IDO expression was detected in CD163 + (M2-type) macrophages infiltrating the tumor microenvironment in Hodgkin lymphoma, and associated with shortened survival in these patients (71).…”
Section: Immune Cellsmentioning
confidence: 63%
“…However, not all patients obtained substantial benefit from ICI treatment. Importantly, a recent study suggested that IDO enzyme might represent a suitable target in this particular clinical context to enhance the efficacy of ICIs in the brain, being a major product of macrophage/microglia populations infiltrating the TME of melanoma metastases in the central nervous system [ 138 ].…”
Section: Clinical Trials Combining Immune Checkpoint Inhibitors Anmentioning
confidence: 99%